Public university strategies in Latin America during the COVID-19 pandemic - Hidalgo-Benites, Lilliam E. (2021)
The COVID-19 pandemic led to the suspension of classes and the closure of university premises to prevent the spread and death of teachers and students, and forced the governments of the countries to implement rapid measures that allow the adaptation of teaching-learning processes to remote education. At the end of 2020, it is considered necessary to fulfill the objective of analyzing the strategies that were implemented, their results and thus determine the future challenges that governments will have to face in the face of reality. To this end, a qualitative research methodology of documentary content analysis was applied to a sample of 28 texts dealing with the subject; some of them were research texts and others were documents of a legal nature from three selected countries: Peru, Colombia and Chile. Five categories of analysis were established to order the results, which showed that the three countries implemented similar educational strategies, such as: adopting virtual distance education using virtual platforms such as learning environments, training teachers and students in digital skills and distribution of tablets and mobile phones with Internet service to students, among others.